Impacts on Colombia's food system caused by natural phenomena: The case of Rosas, Cauca - Castillo, Johana M.; González Rodriguez, Carlos Eduardo (CGIAR System Organization, 2023)
The food system is a complex set of processes involving the production and consumption of food, influenced by economic, social, political, environmental, and demographic factors. Recently, an example of this was experienced in Colombia, where a landslide on the Pan-American Highway in Rosas, southern Cauca, disrupted the connection between municipalities near the landslide and those in the Nariño department, weakening a portion of the agricultural supply system.